BALANCING PROFITS AND RESPONSIBILITY: THE ROLE OF COST-BENEFIT ANALYSIS IN BUSINESS DECISION MAKING [MENYEIMBANGKAN KEUNTUNGAN DAN TANGGUNG JAWAB: PERAN ANALISIS BIAYA-MANFAAT DALAM PENGAMBILAN KEPUTUSAN BISNIS] - Hayatul Khairul Rahmat (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
Cost-benefit analysis (CBA) is a crucial tool in strategic decision-making in the business world, given the challenges and complexities faced by managers when making choices that have significant financial, operational, and reputational consequences. This paper explores the application of CBA in various areas of business management, such as pricing strategies, sustainability, technology adoption, and mergers & acquisitions. Additionally, the paper presents case studies demonstrating how CBA helps companies make decisions balancing short-term costs with long-term benefits, while considering non-financial factors such as environmental impact and corporate reputation. Although CBA is highly beneficial, this paper also acknowledges its limitations, particularly in monetizing intangible benefits and assessing long-term impacts.